PENGARUH PENGEMBANGAN KARIR DAN KOMPETENSI TERHADAP KINERJA GURU DI SMK MANAJEMEN PENERBANGAN MEDAN - Julkarnain .; Mintarsih . (Manajemen dan Bisnis, 2020)
The purpose of the study was to determine the development progress towards teachers in the Medan Aviation Management Vocational School. To determine the effect of competence on the performance of teachers in SMK Flight Management Medan. To find out career development and competence on teacher performance in SMK Flight Management Medan. The population is all teachers obtained by 41 people. The sampling technique is total sampling. The research results obtained from positive and significant career development on teacher performance. Positive competence does not significantly influence teacher performance. Improved teacher performance significantly and significantly to teacher performance.